ANALISIS KEBUTUHAN NUTRIEN DAN EFISIENSI PENGGUNAAN PAKAN BUBUR FORMULASI PADA OPOSUM LAYANG (PETAURUS BREVICEPS WATERHOUSE, 1839) - Farida, Wartika Rosa; Sari, Andri Permata; Inayah, Nurul; Nugroho, Herjuno Ari (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTThe aims of the research was to analyze nutrient requirements, performance, and feed efficiency of porridge formulation on sugar gliders (Petaurus breviceps) based on daily feed intake and digestibility. The research was conducted at the Small Mammal Captivity of Zoology Division, Research Center for Biology, Indonesian Institute of Sciences (LIPI) Cibinong, Bogor. Descriptive method was used in this experiment, with 14 days of preliminary period and 70 days (10 weeks) of data collection. The research materials were 16 sugar gliders aged about 3-5 months and randomly divided into 2 treatments ie. 8 heads were given porridge formulation I (P0 - control treatment) and 8 heads were given porridge formulation II (PI) plus superworm 2 times a week. Estimation of feed digestibility done in vivo with the method of the feces total collection. Variables of this experiment are daily feed intake, nutrient requirement, total digestible nutrients (TDN), daily weight gain, and feed efficiency. The feedstuff of the porridge formulation consist of siamese banana (Musa sp.), watermelon (Citrullus lanatus), sweet potatoes (Ipomoea batatas), grape (Vitis vinifera), pear (Pyrus pyrifolia), boiled egg yolk, baby porridge, calcium, honey, boiled chicken meat, and superworm (Zophobas atratus). The results showed dry matter intake was 5.82 g/head / day or 29.31 g/head / day BB0.75 (P0) and 7.31 g/head/day or 34.16 g/head/day BB0.75 (PI). The average of body weight gain was 0.55 g / head / week (P0) and 0.73 g/head/week (PI) with feed efficiency ratio was 1.36% (P0) and 1.43% (PI). The PI treatment of porridge formulation II has improved the performance of sugar gliders in captivity.Keywords: Daily feed intake, weight gain, porridge formulation, sugar gliders, performance